Economic Disinformation — Causes and Recommendations for Action - Sebastian Blesse; Friedrich Heinemann; Tommy Krieger (Wirtschaftsdienst)
Abstract This articles exploits the results of several Perils-of-Perception studies to investigate how informed the German population is about key economic facts. There are significant misperceptions and Germany ranks in the middle of the group of advanced economies. Our overview briefly sketches different possible explanations for the relatively low factual knowledge of the German society. We propose seven measures that may help to improve the level of economic literacy in Germany, both among young people as well as in the broader segments of the population. Our measures address different stakeholders, such as policymakers, the media and the academic community.